Development of Virtual Reality Media for Earthquake Simulation - Ulum, Muhammad Bahrul; Prasetyaningsih, Prasetyaningsih; Akbar, Anthonio; Hamzah, Raseeda; Wahyudin, Wahyudin; Riza, Lala Septem (CV. Media Inti Teknologi, 2025)
Background: Indonesia has a high risk of earthquakes, necessitating innovative approaches to disaster mitigation education.Aims: This study aims to develop Virtual Reality (VR)-based learning media to enhance students’ understanding and preparedness, particularly among students, in facing earthquake scenarios.Methods: The development process comprises four main stages: identifying educational content, designing interactive scenarios, creating 3D assets and interactive elements, and developing the virtual reality application using Unity.Results: The developed interactive VR media includes a tutorial feature, selectable earthquake location scenario (classroom, library, laboratory), and adjustable earthquake magnitude settings. It enables users to experience immersive and safe earthquake simulations while actively practicing appropriate emergency response procedures.Conclusion: The application of VR-based learning media offers substantial potential to enhance disaster literacy, increase student engagement, and create more meaningful learning experiences. The implementation of this media in educational settings is expected not only to strengthen a culture of disaster awareness but also to contribute to reducing casualties and losses caused by earthquakes in the future.